Characterising the potential of sheep wool for ancient DNA analyses - Luise Ørsted Brandt; Lena Diana Tranekjer; Ulla Mannering; Maj Ringgaard; Karin Margarita Frei; Eske Willerslev; Margarita Gleba; M. Thomas P. Gilbert (Archaeological and Anthropological Sciences, 2011)
The use of wool derived from sheep (Ovis aries) hair shafts is widespread in ancient and historic textiles. Given that hair can represent a valuable source of ancient DNA, wool may represent a valuable genetic archive for studies on the domestication of the sheep. However, both the quality and content of DNA in hair shafts are known to vary, and it is possible that common treatments of wool such as dyeing may negatively impact the DNA. Using quantitative real-time polymerase chain reaction (PCR), we demonstrate that in general, short fragments of both mitochondrial and single-copy nuclear DNA can be PCR-amplified from wool derived from a variety of breeds, regardless of the body location or natural pigmentation. Furthermore, although DNA can be PCR-amplified from wool dyed with one of four common plant dyes (tansy, woad, madder, weld), the use of mordants such as alum or iron leads to considerable DNA degradation. Lastly, we demonstrate that mtDNA at least can be PCR-amplified, cloned and sequenced from a range of archaeological and historic Danish, Flemmish and Greenlandic wool textile samples. In summary, our data suggest that wool offers a promising source for future ancient mitochondrial DNA studies.